2023
DOI: 10.1038/s41598-023-37146-5
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 2 (PON2) plays a limited role in murine lung tumorigenesis

Abstract: Paraoxonase 2 (PON2) is a multifunctional intracellular enzyme that has received growing attention for its ability to modulate various aspects of normal and malignant cellular physiology. Recent research has revealed that PON2 is upregulated in tissues from patients with various types of solid tumors and hematologic cancers, likely due to its ability to suppress oxidative stress and evade apoptosis. However, the effects of PON2 on pulmonary oncogenesis are unknown. Here, we conducted studies to investigate how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Induced enzyme knockdown and knockout significantly impaired cell proliferation and promoted cell cycle arrest in murine Lewis lung carcinoma (LCC) cell line and human A549 and NCI-HI1299 lung adenocarcinoma cells. Subsequent investigation of the impact of PON2 on cellular bioenergetics and metabolism revealed that enzyme loss markedly reduced glycolysis, tricarboxylic acid cycle activity, and de novo pyrimidine nucleotide biosynthesis [39]. As previously reported, also in lung cancer, PON2 overexpression was found to counteract programmed cell death by balancing ROS production.…”
Section: Pon2 and Other Cancerssupporting
confidence: 59%
See 1 more Smart Citation
“…Induced enzyme knockdown and knockout significantly impaired cell proliferation and promoted cell cycle arrest in murine Lewis lung carcinoma (LCC) cell line and human A549 and NCI-HI1299 lung adenocarcinoma cells. Subsequent investigation of the impact of PON2 on cellular bioenergetics and metabolism revealed that enzyme loss markedly reduced glycolysis, tricarboxylic acid cycle activity, and de novo pyrimidine nucleotide biosynthesis [39]. As previously reported, also in lung cancer, PON2 overexpression was found to counteract programmed cell death by balancing ROS production.…”
Section: Pon2 and Other Cancerssupporting
confidence: 59%
“…It was demonstrated that PON2 upregulation can positively influence different processes associated with intracellular metabolism, such as glucose intake and consumption through glycolysis (and not by the pentose phosphate pathway), as well as the tricarboxylic acid cycle (TCA) and pyrimidine nucleotide biosynthesis. A high intracellular glucose level together with downstream intermediates of the glycolytic and TCA pathways contribute to the inhibition of AMP-activated protein kinase (AMPK), which in turn promotes tumor growth and metastasis [38,39].…”
Section: Pon2 and Cancermentioning
confidence: 99%
“…Paraoxonase-2 ( PON2 ) is another notable biomarker, with significant upregulation observed in melanomas compared to control nevi. PON2 expression correlates with important prognostic parameters, indicating its potential as a prognostic biomarker and its involvement in melanoma cell resistance to chemotherapy [ 122 , 123 , 124 ]. Moreover, the transcription factor Nrf2 has been linked to an altered redox homeostasis in melanomas, influencing phenotype switching.…”
Section: Future Directionsmentioning
confidence: 99%
“… 4 Studies have shown that PON2 expression is upregulated in tumor tissues compared with their corresponding normal tissues across various cancer types, including ovarian, breast, prostate, lung, colon, bladder, and leukemia. 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…PON2 , a multifunctional enzyme, has gained attention because of its involvement in cellular homeostasis, lipid metabolism, and antiapoptotic properties 4 . Studies have shown that PON2 expression is upregulated in tumor tissues compared with their corresponding normal tissues across various cancer types, including ovarian, breast, prostate, lung, colon, bladder, and leukemia 5–7 …”
Section: Introductionmentioning
confidence: 99%